Aristolone content analysis in ficus auriculata as predicted apoptotic activity in hela cells - Kusmayra Ambarwati; Miftahul Jannah; Asyifa Robiatul Adawiyah (Universitas Aisyiyah Yogyakarta, 2021)
Antioxidants and herbs have been scientifically proven to be one of the substances that can prevent cervical cancer. The incidence of cervical cancer in Indonesia is very high and is a vital cause of death of women in Indonesia. Every day 40-45 new cases emerge, which means 20-25 people die from cervical cancer in Indonesia. Several previous studies have shown that there are plants, fruits and seeds that contain high antioxidants and are believed to prevent and reduce pain due to cervical cancer. Besides, many herbs that also found in Indonesia are known to affect cancer cells. Ficus auriculata can find in Indonesia. However, not many people use the available natural resources that are suspected to prevent cervical cancer. This study was a preliminary study analyzed of Aristolone in Ara Fruit used as a prediction of apoptosis in HeLa cells. The results showed that the positive effect of Aristolone content in F. auriculata affected proliferation supported by previous studies.